Evaluation of the perception of mental health of professionals in an intensive care unit in coping with COVID-19 from 2020 to 2022 (Research, Society and Development, 2022)
Objectives: To evaluate the perception of health professionals in the ICU in coping with COVID-19 on mental health. Methodology: This is a narrative review of the literature, whose descriptors used were “COVID-19”, “health professionals”, “intensive care unit” and “mental health”, their combinations and variants in English. The databases chosen were the National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Literature in Health Sciences (LILACS), in addition to Google Scholar as a complementary database. Full articles available online, in English or Portuguese, published between 2020 and 2022 and answering the guiding question of the study were selected. Results and Discussion: Anxiety, irritability, insomnia, fear and anguish were the most observed signs and symptoms during the pandemic, probably related to the extremely high workload and lack of personal protective equipment. The profile of professionals with symptoms compatible with a possible diagnosis of generalized anxiety disorder (GAD) are the youngest, with less professional experience, who work fewer hours, who have temporary jobs, who work in rotation and who need to care for more than 20 hours. patients with COVID-19. Conclusion: the COVID-19 pandemic has had negative repercussions on the mental health of health professionals working in the ICU. Service overload, associated with emotional fragility when dealing with hospitalized patients and their families, caused health professionals to develop (or worsen) psychological and/or psychiatric problems.